Hygrocybe pellucida—a new species of Hygrophoraceae from Kerala State, India - Latha, K. P. Deepna; Haridev, P.; Raj, K. N. Anil; Manimohan, Patinjareveettil (Phytotaxa, 2024)
Hygrocybe pellucida sp. nov. is described from Kerala State, India based on both morphology and multigene phylogenetic analyses (nrITS, nrLSU). This species is characterized by small, viscid, translucent basidiocarps, a whitish to grayish pileus with reddish pellucid striations, dimorphic basidiospores and basidia, a sterile lamella edge with abundant pseudocystidia, an ixotrichoderm-type pileipellis and an ixocutis-type stipitipellis. A comprehensive species description along with photographs of both the basidiocarps and the microscopic features, line drawings of the microscopic structures, a comparison with morphologically similar and phylogenetically related species and phylogenetic trees inferring the placement of the new species within the section Velosae are provided.